2007
DOI: 10.1097/qad.0b013e3281532ca7
|View full text |Cite
|
Sign up to set email alerts
|

Increased duration of viral suppression is associated with lower viral rebound rates in patients with previous treatment failures

Abstract: After around 4 years of viral suppression rebound rates in individuals with multiple prior treatment failures approach those of individuals with no prior treatment failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
29
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 17 publications
11
29
0
1
Order By: Relevance
“…After adjustment, time since last viral rebound was highly predictive of virological failure after starting new ARVs, consistent with findings from other studies. For example, Benzie et al [16] reported that up to 4 years of sustained viral suppression was necessary in patients with previous treatment failures for them to achieve rebound rates similar to those of patients with no prior treatment failures. The greatest risk of viral rebound has been shown to be in the first few months after initial suppression [14], and therefore it follows that increasing time since last virological rebound decreased the risk of virological failure after baseline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After adjustment, time since last viral rebound was highly predictive of virological failure after starting new ARVs, consistent with findings from other studies. For example, Benzie et al [16] reported that up to 4 years of sustained viral suppression was necessary in patients with previous treatment failures for them to achieve rebound rates similar to those of patients with no prior treatment failures. The greatest risk of viral rebound has been shown to be in the first few months after initial suppression [14], and therefore it follows that increasing time since last virological rebound decreased the risk of virological failure after baseline.…”
Section: Discussionmentioning
confidence: 99%
“…This proportion has increased in recent years [11][12][13]; however, viral replication is still not fully controlled in all patients at all times. Previous analyses have found that a patient is most likely to fail in the first few months after initial viral suppression [14], that increasing time with viral suppression decreases the risk of rebound [15,16], and that treatment interruptions with detectable viral load [17] increase the risk of rebound, as does pre-cART exposure to nucleoside reverse transcriptase inhibitor (NRTI) regimens [15,18]. Additionally, low CD4 cell counts, high viral load, a slow virological response to cART and prior AIDS diagnosis were linked to lack of durable viral load undetectability [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Individuals were again included in the analysis if and when they next achieved a viral load o50 copies/mL whilst receiving cART and hence started a new suppression episode. At the start of each suppression episode, the number of previous ARV regimens that had been failed was calculated using a definition from a previous study [10]. A treatment regimen was failed on each date an individual experienced a viral load 4400 copies/mL and there was an ARV they hadn't failed previously in a current regimen they had been receiving for 416 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…However, the expected duration of viral suppression in this situation remains unclear. A recent study by Benzie et al [10] for the UK Collaborative HIV Cohort (CHIC) found a strong association between a higher number of previous treatment regimens failed and raised risk of viral rebound.…”
Section: Introductionmentioning
confidence: 99%
“…Entre los efectos adversos como causa de cambio de terapia destacaron la alergia y las dislipidemias; estas últimas son importantes pues su incidencia se mantiene similar a pesar de nuevos medicamentos. Las consecuencias cardiovasculares de la tri-terapia han sido destacadas en muchas series 5,7,8 aunque no pudieron ser evaluadas sistemáticamente en esta población. Otro efecto adverso frecuentemente descrito en este grupo fue la lipodistrofia, especialmente la atrofia del tejido graso de la cara y las extremidades.…”
Section: Discussionunclassified